Microbiological research in agroecosystem management - Rajesh Kannan, Velu; Ohio Library and Information Network (New York : Springer, 2013)
Agroecosystem is an ideal dynamic functional system with a set of chemical and biological interaction taking place in plant surface either below or above the ground levels. These levels of interaction activities fundamentally with microorganism-plant-soil systems are extended upto the level of entire agricultural economy. Greatly simplified, the agroecosystems control the various range of energy flux, resources exchange, organic and inorganic nutrient budgets and population dynamics.The main aim of this edited volume is to provide a broad spectrum of agroecosystems structure, function and maintenance involved in microbial research. This book consists of 20 full length research articles focusing on the emerging problems in the field and the positive findings are identified on key areas of research such as biodiversity, ecosystem service, environmental cleaning in agroecology, etc. These articles are arranged progressively linking themselves thematically with photographs, figures and tables. Focused field articles are included which prove a valuable contribution to the field of agroecosystem management by microbial facilitations. The editor hopes that these articles would prompt the budding scholars to further their research which in turn would certainly help the agriculturists
Includes bibliographical references and index
Keywords: Agricultural microbiology -- Congresses; Agriculture -- Congresses; Microbiology -- Congresses